Treatment with pyrophosphate inhibits uremic vascular calcification - O’Neill, W. Charles (2010)
Pyrophosphate, which may be deficient in advanced renal failure, is a potent inhibitor of vascular calcification. To explore its use as a potential therapeutic, we injected exogenous pyrophosphate subcutaneously or intraperitoneally in normal rats and found that their plasma pyrophosphate concentrations peaked within 15 min. There was a single exponential decay with a half-life of 33 min. The kinetics were indistinguishable between the two routes of administration or in anephric rats. The effect of daily intraperitoneal pyrophosphate injections on uremic vascular calcification was then tested in rats fed a high-phosphate diet containing adenine for 28 days to induce uremia. Although the incidence of aortic calcification varied and was not altered by pyrophosphate, the calcium content of calcified aortas was significantly reduced by 70%. Studies were repeated in uremic rats given calcitriol to produce more consistent aortic calcification and treated with sodium pyrophosphate delivered intraperitoneally in a larger volume of glucose-containing solution to prolong plasma pyrophosphate levels. This maneuver significantly reduced both the incidence and amount of calcification. Quantitative histomorphometry of bone samples after double-labeling with calcein indicated that there was no effect of pyrophosphate on the rates of bone formation or mineralization. Thus, exogenous pyrophosphate can inhibit uremic vascular calcification without producing adverse effects on bone.